Strategic Management Accounting, Volume II Beyond the Numbers - Joannidès de Lautour, Vassili (Springer International Publishing, 2018)
This book responds to key issues in strategic management control beyond the numbers. Grounded in research but written with practitioners and students in mind, this second volume addresses the most up-to-date management control issues in the public sector, forecasting, budgeting and controls in international organisations.